Impact of directionality on student interpreters’ performance in consecutive interpreting - Rong, Lu; Abdullah, Muhammad Alif Redzuan; Lay, Hoon Ang (Academy Publication, 2023)
Studies showed that interpreters might differ in performance when it comes to directionality. Nevertheless, limited research has been undertaken concerning the impact of directionality on student interpreters’ performance in consecutive interpreting (CI), a type of interpreting categorised by the working mode. This study aims to investigate the relationship between directionality and performance by adopting a quantitative approach. Four student interpreters from a Chinese university were selected as samples with a homogeneity sampling method. The participants used Chinese as their first language (L1, or A language) and English as a second language (L2, or B language). Analytic rating scales were combined with propositional analysis to assign scores for different aspects of accuracy and completeness in the product of the CI test by student interpreters. To determine the impact of directionality on performance, paired samples t-test was adopted in the current study by testing the significance of the difference between two mean scores of the CI test. The results showed that directionality affected the performance of student interpreters. Overall, the participants performed better in the into-B direction than in the into-A direction. Thus, it is recommended that teachers pay more attention to training listening comprehension ability of the source text in into-A direction.